Strategi Pemasaran UMKM Roti Al Batsit Kota Bengkulu - Susena, Karona Cahya; Herlika, Eren herlika; Roziana, Refsi; Efendi, Fithria Habib (Jurnal Kewirausahaan & Inovasi, 2024)
Roti Al Batsit MSME is a small business engaged in the food industry located in Bengkulu City. As one of the MSMEs, the challenge that must be faced is how to increase product sales and introduce the Roti Al Batsit brand to the public. Therefore, a community service programme entitled " Marketing Strategy for UMKM Bread Al Batsit Bengkulu City " was conducted to assist business managers in designing marketing strategies that suit the characteristics of their business. This programme aims to increase product sales and introduce the Roti Al Batsit brand to the community.The implementation of marketing strategies is carried out with several steps, such as creating a brand identity for Roti Al Batsit, using social media as a means of promotion, developing a distribution network. Brand identity was created to introduce the Roti Al Batsit brand more clearly and present in the market, while the use of social media was carried out so that consumers easily recognise and remember the Roti Al Batsit brand and give a positive image to the brand. The development of a distribution network is carried out to expand market share and expand the reach of products to consumers. From the evaluation results, the community service programme with the title " Marketing Strategy for UMKM Bread Al Batsit Bengkulu City " succeeded in having a positive impact on the continuity of the MSME business. The implementation of the right marketing strategy has succeeded in increasing the number of product sales and increasingawareness of the Roti Al Batsit brand in the community. In addition, the programme also helps MSMEs to expand their distribution network and optimise the use of social media as a promotional tool. Thus, the implementation of effective marketing strategies can be a solution for MSMEs in facing increasingly competitive market competition.